A method for preparing silicified microcrystalline cellulose based on wet granulation
Silicated microcrystalline cellulose is prepared by wet granulation method, which solves the problems of high energy consumption, large equipment investment and limited fluidity in the prior art, achieves lower energy consumption and better fluidity, and improves the material processing process of the direct tableting process.
Patent Information
- Application Number
- CN202510068446.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing preparation methods of silicide microcrystalline cellulose have high energy consumption, large equipment investment, and limited product fluidity, which affects the material uniformity and production cycle of the direct tableting process.
The preparation method of silicated microcrystalline cellulose based on wet granulation is adopted. By dispersing colloidal SiO2 in high-temperature water, spraying microcrystalline cellulose into it and using it in combination with cold water, wet granulation is performed, and then drying and pulverizing, the silicated microcrystalline cellulose produced has better fluidity.
It reduces energy consumption and equipment investment, improves the fluidity of silicified microcrystalline cellulose, and improves the material conveying, filling and mixing process in the direct tableting process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical preparation auxiliary materials, and in particular to a method for preparing silicified microcrystalline cellulose based on wet granulation. Background Art
[0002] Silicified microcrystalline cellulose (SMCC) is a pharmaceutical excipient made by pre-mixing and co-processing microcrystalline cellulose and colloidal silicon dioxide through a special process. It is mainly used in direct tableting. Different from the ordinary physical mixing process, in the preparation process of SMCC, the raw materials react in a sub-particle state, producing functional synergy, covering up the shortcomings of a single excipient, and can change the fluidity, compressibility and filling properties of direct compression powder, reducing the content difference of small doses of drugs. SMCC has good fluidity, compressibility and anti-hygroscopicity, and has unique properties such as high load capacity and high disintegration characteristics brought by a large specific surface area. Therefore, it can be used as a functional diluent for direct tableting, solving process problems such as large volume of large-dose tablets and uneven distribution of active ingredients in small-dose tablets, and can meet the formulation requirements of tablet cores, pill cores, orally disintegrating tablets, and dispersible tablets.
[0003] The main preparation method of SMCC at present is to mix microcrystalline cellulose and colloidal silicon dioxide in water and then spray dry to obtain SMCC (for example, patent CN106333928A). The spray drying process has high energy consumption and large equipment investment, and the fluidity of SMCC obtained by the existing method is limited. The fluidity of SMCC will affect the material transportation, filling and mixing processes in the direct tableting process, and thus affect the material uniformity, production cycle and performance differences between tablets of direct compression tablets. Summary of the invention
[0004] In order to solve the above technical problems, namely, the existing method for preparing silicified microcrystalline cellulose has high energy consumption, large equipment investment, and limited product fluidity, the present invention provides a method for preparing silicified microcrystalline cellulose based on wet granulation. The preparation method of the present invention can reduce energy consumption, reduce equipment investment, and the prepared silicified microcrystalline cellulose has better fluidity.
[0005] The specific technical scheme of the present invention is:
[0006] A method for preparing silicified microcrystalline cellulose based on wet granulation comprises the following steps:
[0007] S1: Disperse colloidal SiO2 in water at 60-95°C to obtain colloidal SiO2 dispersion, and keep it warm for later use;
[0008] S2: spraying colloidal SiO2 dispersion and 20-30°C water into microcrystalline cellulose for wet granulation, controlling the speed of the stirring blade to 200-250rpm and the speed of the cutting knife to 1400-1600rpm, to obtain wet granules; the mass ratio of the 20-30°C water in step S2 to the 60-95°C water in step S1 is 1:3.5-7.0;
[0009] S3: Drying and crushing the wet granules to obtain silicified microcrystalline cellulose.
[0010] The present invention adopts a wet granulation method to prepare SMCC. Microcrystalline cellulose is used as a base material, which has good compressibility and certain fluidity; colloidal SiO2 is used as a flow aid, which can improve the fluidity of the material and increase its hygroscopic resistance. In the wet granulation process of the present invention, colloidal SiO2 adheres to the surface and interior of the microcrystalline cellulose particles to form a stable co-processed product structure, namely SMCC. This co-processed product structure can not only retain the original excellent properties of microcrystalline cellulose, but also produce functional synergy between colloidal SiO2 and microcrystalline cellulose, so that SMCC has better fluidity, compressibility and hygroscopic resistance than a single auxiliary material. Compared with the spray drying method, the use of wet granulation to prepare SMCC can reduce energy consumption and reduce equipment investment.
[0011] Generally speaking, compared with the spray drying method, the fluidity of the particles obtained by wet granulation is poor. However, the present invention can make the fluidity of SMCC obtained by wet granulation better than that of SMCC obtained by conventional spray drying method by the comprehensive design of ① using colloidal SiO2 dispersion and 20-30℃ water + ② controlling the speed of the stirring blade and the speed of the cutter during the wet granulation process. Specifically:
[0012] Use colloidal SiO2 dispersion with 20~30℃ water:
[0013] In the whole preparation process of the present invention, two kinds of water at different temperatures are used, which can play the following roles: before wet granulation, colloidal SiO2 is dispersed in water at 60-95°C, and the higher water temperature can soften the colloidal SiO2 particles and the microcrystalline cellulose particles that are subsequently in contact with the colloidal SiO2 dispersion, so that they can better adhere to the surface and interior of the microcrystalline cellulose particles; during the wet granulation process, by spraying 20-30°C water, it is helpful to better disperse the colloidal SiO2 on the surface and interior of the microcrystalline cellulose particles, forming a more uniform co-processed product structure. In the above manner, the colloidal SiO2 dispersion and the 20-30°C water phase are combined, which is conducive to the attachment of colloidal SiO2 to the surface and interior of the unprocessed cellulose particles, thereby promoting the colloidal SiO2 to play its role in improving the fluidity of the material, so that the prepared SMCC has better fluidity.
[0014] Based on the effects of the two different temperatures of water, the usage ratio between the two will affect the fluidity of SMCC. When the mass ratio of 20-30℃ water to 60-95℃ water is controlled at 1:3.5-7.0, the latter can effectively soften the colloidal SiO2 and microcrystalline cellulose particles, and the former can promote dispersion, thereby achieving better fluidity of SMCC.
[0015] ②Control the speed of the stirring blade and the cutting blade during the wet granulation process:
[0016] By matching the appropriate stirring blade speed and cutting blade speed, the combination between microcrystalline cellulose and colloidal SiO2 can be made closer, and the water at a certain temperature contained on the surface of SMCC during the wet granulation process can be used to make the surface of the prepared SMCC smoother, thereby improving the fluidity of SMCC.
[0017] Preferably, in step S1, the temperature of the water is 70-90°C.
[0018] In the process of preparing colloidal SiO2 dispersion before wet granulation, when the water temperature used is too low, it is not conducive to the softening of colloidal SiO2 and microcrystalline cellulose particles, and will affect the adhesion of colloidal SiO2 on microcrystalline cellulose particles, thereby making the fluidity of SMCC lower; and when the water temperature used is too high, a strong binding force will be formed between the colloidal SiO2 in the dispersion, which is not conducive to the dispersion of colloidal SiO2 to the surface and inside of microcrystalline cellulose particles during subsequent wet granulation, so it will also have an adverse effect on the fluidity of SMCC. The present invention can further improve the fluidity of SMCC by controlling the water temperature at 70~90℃.
[0019] Preferably, in step S2, the particle size of the microcrystalline cellulose is 80-100 μm; in step S1, the specific surface area of the colloidal SiO2 is 150-380 m 2 / g.
[0020] Preferably, in step S2, during the wet granulation process, the speed of spraying the colloidal SiO2 dispersion is 250-350 mL / min, the time of spraying the colloidal SiO2 dispersion and 20-30°C water is the same, and the stirring paddle and scraper are turned off 5-10 minutes after spraying the colloidal SiO2 dispersion and 20-30°C water.
[0021] Preferably, in step S3, before the drying, the wet granules are sized using a 40-60 mesh sieve; after the pulverization, the granules are sized again and sieved to obtain silicified microcrystalline cellulose with a particle size of 100-120 mesh.
[0022] Preferably, in steps S1 and S2, the mass ratio of the colloidal SiO2 to the microcrystalline cellulose is 1:15-49, and the ratio of the total mass of the colloidal SiO2 and the microcrystalline cellulose to the total mass of the water at 60-95°C and the water at 20-30°C is 1:1.0-1.5.
[0023] Preferably, the specific process of step S2 includes: adding microcrystalline cellulose into a wet granulator, turning on a stirring blade and a cutting knife, and then spraying a colloidal SiO2 dispersion and 20-30°C water into the wet granulator to perform wet granulation.
[0024] Preferably, the specific process of step S1 includes: stirring the colloidal SiO2 and 60-95°C water at a rotation speed of 750-1000 rpm for 5-10 minutes to obtain a colloidal SiO2 dispersion.
[0025] Preferably, in step S2, the moisture content of the microcrystalline cellulose is 4-5%.
[0026] Preferably, in step S3, the drying temperature is 90-95° C. and the drying time is 2.5-3.5 h.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] (1) The present invention adopts a wet granulation method to prepare silicified microcrystalline cellulose, which can reduce energy consumption and equipment investment.
[0029] (2) The silicified microcrystalline cellulose prepared by the preparation method of the present invention has good fluidity, which can facilitate the transportation, filling and mixing of materials when used in the direct tableting process.
[0030] (3) The silicified microcrystalline cellulose prepared by the preparation method of the present invention has good compressibility and can give the powder direct compression tablets good formability. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with the embodiments.
[0032] A method for preparing silicified microcrystalline cellulose based on wet granulation comprises the following steps:
[0033] S1: Disperse colloidal SiO2 in water at 60-95°C to obtain colloidal SiO2 dispersion, and keep it warm for later use;
[0034] S2: spraying colloidal SiO2 dispersion and 20-30°C water into microcrystalline cellulose for wet granulation, controlling the speed of the stirring blade to 200-250rpm and the speed of the cutting knife to 1400-1600rpm, to obtain wet granules; the mass ratio of the 20-30°C water in step S2 to the 60-95°C water in step S1 is 1:3.5-7.0;
[0035] S3: Drying and crushing the wet granules to obtain silicified microcrystalline cellulose.
[0036] In some specific embodiments, the specific process of step S1 includes: stirring the colloidal SiO2 and 60-95°C water at a rotation speed of 750-1000 rpm for 5-10 minutes to obtain a colloidal SiO2 dispersion.
[0037] In some specific embodiments, the specific process of step S2 includes: adding microcrystalline cellulose to a wet granulator, turning on a stirring blade and a cutting knife, and then spraying a colloidal SiO2 dispersion and 20-30°C water into the wet granulator to perform wet granulation.
[0038] In some specific embodiments, in step S2, during the wet granulation process, the speed of spraying the colloidal SiO2 dispersion is 250-350 mL / min, the time of spraying the colloidal SiO2 dispersion and 20-30°C water is the same, and the stirring paddle and scraper are turned off 5-10 minutes after spraying the colloidal SiO2 dispersion and 20-30°C water.
[0039] In some specific embodiments, in step S1, the temperature of the water is 70-90°C.
[0040] In some specific embodiments, in step S2, the particle size of the microcrystalline cellulose is 80-100 μm, and the moisture content is 4-5%; in step S1, the specific surface area of the colloidal SiO2 is 150-380 m 2 / g. Under the above design, the particle size of microcrystalline cellulose matches the specific surface area of colloidal SiO2, which can make the binding sites between the two more easily contact each other, thereby improving the binding effect, which helps to improve the fluidity and compressibility of SMCC. The above is only used as a specific embodiment. The present invention does not limit the particle size of microcrystalline cellulose, and it can be adjusted according to the specific needs of the preparation. For example, for large-dose preparations that require a high drug loading, microcrystalline cellulose with a smaller particle size can be used to provide more specific surface area, thereby improving the drug loading capacity of silicified microcrystalline cellulose; for small-dose preparations with a low drug loading, microcrystalline cellulose with a larger particle size can be used.
[0041] In some specific embodiments, in steps S1 and S2, the mass ratio of the colloidal SiO2 to the microcrystalline cellulose is 1:15-49, and the ratio of the total mass of the colloidal SiO2 and the microcrystalline cellulose to the total mass of the water at 60-95°C and the water at 20-30°C is 1:1.0-1.5.
[0042] In some specific embodiments, in step S3, before the drying, the wet granules are sized using a 40-60 mesh screen; after the pulverization, the granules are sized again and sieved to obtain silicified microcrystalline cellulose with a particle size of 100-120 mesh. The above is only a specific embodiment. Under the method of the present invention, the particle size and bulk density of the finally obtained silicified microcrystalline cellulose can be flexibly changed according to demand.
[0043] In some specific embodiments, in step S3, the drying temperature is 90-95° C. and the drying time is 2.5-3.5 h.
[0044] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0045] In the following examples and comparative examples, the information related to the instruments and reagents used is shown in Table 1 and Table 2, but the protection scope of the present invention is not limited thereto.
[0046] Table 1 Instrument models and sources
[0047]
[0048] Table 2 Sources of reagents
[0049]
[0050] Example 1: Preparation of SMCC based on wet granulation
[0051] The silicified microcrystalline cellulose was prepared by the following steps (the amount of each raw material was measured by weight):
[0052] S1: 4 parts of colloidal silica (specific surface area 380m 2 / g) and 100 parts of 90°C purified water were put into a homogenizer and stirred at a speed of 1000 rpm for 5 minutes to obtain a colloidal silica dispersion, which was kept warm for later use.
[0053] S2: 96 parts of microcrystalline cellulose (particle size of 80-100 μm, moisture content of 5%) are put into a wet granulator, the stirring paddle speed is set to 200 rpm, the cutting knife speed is set to 1500 rpm, the stirring paddle and the cutting knife are turned on, and then the colloidal SiO2 dispersion prepared in step S1 under insulation is sprayed into the wet granulator at a speed of 300 mL / min, and 20 parts of 25°C purified water are sprayed at the same time. The time for spraying the colloidal SiO2 dispersion and the 25°C purified water is the same. After 5 minutes of spraying, the stirring paddle and the cutting knife are turned off to obtain wet granules.
[0054] S3: Use a sieve with a pore size of 40 mesh (380 μm) to size the wet granules.
[0055] S4: Dry the wet granules after completing step S3 at a drying temperature of 95° C. for 3 hours to obtain dry granules.
[0056] S5: After the dry particles are crushed, they are sized and sieved to obtain silicified microcrystalline cellulose with a particle size of 100-120 meshes.
[0057] According to the method of this example, three batches of silicified microcrystalline cellulose (300 g for each batch) were prepared.
[0058] The three batches of silicified microcrystalline cellulose prepared in this example were subjected to performance tests, including bulk density, tap density, compression, drop cone height and repose angle, and the results were averaged over the three batches. The performance test results are shown in Table 3.
[0059] The three batches of silicified microcrystalline cellulose prepared in this example were tableted, the tablet weight was preset to 500 mg, the mold was 11 mm flat punch, and the pressure was 200 bar. 20 tablets were prepared from each batch of silicified microcrystalline cellulose, and the thickness and hardness of the prepared direct compression tablets were tested, and the results were averaged. The test results of the direct compression tablets are shown in Table 3.
[0060] Comparative Example 1: Preparation of SMCC based on spray drying
[0061] In this comparative example, silicified microcrystalline cellulose was prepared by conventional spray drying method, and the specific steps are as follows (the amount of each raw material is calculated by weight):
[0062] S1: 4 parts of colloidal silica (specific surface area 380m 2 / g) and 120 parts of water were put into a homogenizer and homogenized at a speed of 7800 rpm for 30 minutes. Then 96 parts of microcrystalline cellulose (particle size of 80-100 μm, moisture content of 5%) were added and stirred at a speed of 1000 rpm for 5 minutes to obtain a slurry.
[0063] S2: The slurry was subjected to airflow double-fluid spray drying, with the air inlet temperature set at 160°C, the air outlet temperature set at 85°C, the atomization pressure set at 0.2 bar, and the liquid inlet speed set at 500 ml / H to obtain dry particles.
[0064] S3: The dry particles are sieved to obtain silicified microcrystalline cellulose with a particle size of 40-60 μm.
[0065] According to the method of this comparative example, 3 batches of silicified microcrystalline cellulose (300 g for each batch) were prepared. According to the method in Example 1, the 3 batches of silicified microcrystalline cellulose prepared in this comparative example were tested for performance, and direct compression tablets were prepared to test the thickness and hardness of the direct compression tablets. The test results are shown in Table 3.
[0066] Table 3 Effect of preparation method on SMCC properties
[0067]
[0068] Analyzing the data in Table 3, we can see that:
[0069] The angle of repose of Example 1 is smaller than that of Comparative Example 1, and the degree of compression is greater than that of Comparative Example 1. This indicates that compared with the existing spray drying method, the method of the present invention can make the prepared SMCC have better fluidity and compressibility.
[0070] Examples 2-7 and Comparative Examples 2-3: Effect of water temperature on SMCC performance
[0071] In Examples 2 to 5 and Comparative Example 2, silicified microcrystalline cellulose was prepared according to the steps of Example 1, and the only difference from Example 1 was that the temperature of purified water used in step S1 was changed. The specific settings are shown in Table 4.
[0072] In Examples 6-7 and Comparative Example 3, silicified microcrystalline cellulose was prepared according to the steps of Example 1, and the only difference from Example 1 was that the temperature of purified water used in step S2 was changed. The specific settings are shown in Table 5.
[0073] According to the methods of Examples 2 to 7 and Comparative Examples 2 to 3, three batches of silicified microcrystalline cellulose (300 g for each batch) were prepared. According to the method in Example 1, the three batches of silicified microcrystalline cellulose prepared in Examples 2 to 7 and Comparative Examples 2 to 3 were tested for performance, and direct compression tablets were prepared to test the thickness and hardness of the direct compression tablets. The test results are shown in Tables 4 and 5.
[0074] Table 4 Effect of step S1 water temperature on SMCC performance
[0075]
[0076] Table 5 Effect of step S2 water temperature on SMCC performance
[0077]
[0078] Analyzing the data in Table 4, we can see that:
[0079] (1) In the process of preparing colloidal silica dispersion before wet granulation, using hot water at 60-95°C can improve the fluidity of the obtained SMCC (making the measured angle of repose smaller) compared with water at room temperature, and can make the fluidity of SMCC obtained by wet granulation higher than that by spray drying. This is because: higher water temperature can soften the colloidal silica particles and the microcrystalline cellulose particles that are subsequently in contact with the hot colloidal silica dispersion, so that they can better adhere to the surface and interior of the microcrystalline cellulose particles, promoting the colloidal silica to play its role in improving the fluidity of the material.
[0080] (2) In the process of preparing colloidal silica dispersion before wet granulation, the fluidity of SMCC can be further improved (the angle of repose of SMCC can be reduced) by controlling the water temperature at 70-90°C. This is because: when the water temperature used is too low, it is not conducive to the softening of colloidal silica and microcrystalline cellulose particles, which will affect the adhesion of colloidal silica on microcrystalline cellulose particles, thereby reducing the fluidity of SMCC; when the water temperature used is too high, a strong binding force will be formed between the colloidal silica in the dispersion, which is not conducive to the dispersion of colloidal silica to the surface and inside of microcrystalline cellulose particles during subsequent wet granulation, so it will also have an adverse effect on the fluidity of SMCC.
[0081] Analyzing the data in Table 5, we can see that:
[0082] During the wet granulation process, spraying 20-30°C water while spraying colloidal SiO2 dispersion can improve the fluidity of the obtained SMCC (making the measured repose angle smaller); when the sprayed water temperature is too high, the fluidity of the obtained SMCC decreases. This is because: spraying 20-30°C water helps to better disperse the colloidal SiO2 on the surface and inside of the microcrystalline cellulose particles, forming a more uniform co-processed product structure.
[0083] Examples 8-9 and Comparative Examples 4-7: Effect of the ratio of two parts of water on the performance of SMCC
[0084] In Examples 8 to 9 and Comparative Examples 4 to 7, silicified microcrystalline cellulose was prepared according to the steps of Example 1, and the only difference from Example 1 was that the amount of purified water in Steps S1 and S2 was changed, and the specific settings are shown in Table 6 (the amount of purified water is in parts by weight). Among them, the amount of purified water in Step S1 of Comparative Example 4 is 0 parts, and the amount of purified water in Step S2 is 120 parts, which means that Step S1 is not performed, and colloidal silicon dioxide is put into the wet granulator together with microcrystalline cellulose in Step S2.
[0085] According to the methods of Examples 8-9 and Comparative Examples 4-7, three batches of silicified microcrystalline cellulose (300 g for each batch) were prepared. According to the method in Example 1, the three batches of silicified microcrystalline cellulose prepared in Examples 8-9 and Comparative Examples 4-7 were tested for performance, and direct compression tablets were prepared to test the thickness and hardness of the direct compression tablets. The test results are shown in Table 6.
[0086] Table 6 Effect of the ratio of two parts of water on the performance of SMCC
[0087]
[0088] Analyzing the data in Table 6, we can see that:
[0089] (1) The present invention uses two parts of water at specific temperatures to improve the fluidity of SMCC (making the measured angle of repose smaller). This is because: hot water is used to disperse the colloidal silica before wet granulation. The higher water temperature can soften the colloidal silica particles and the microcrystalline cellulose particles that are subsequently in contact with the colloidal silica dispersion, thereby allowing them to better adhere to the surface and interior of the microcrystalline cellulose particles; during the wet granulation process, spraying water at room temperature helps to better disperse the colloidal silica on the surface and interior of the microcrystalline cellulose particles, forming a more uniform co-processed product structure. In this way, the hot colloidal silica dispersion and room temperature water are combined, which is conducive to the adhesion of colloidal silica to the surface and interior of the ungranulated cellulose particles, thereby promoting the colloidal silica to play its role in improving the fluidity of the material, so that the prepared SMCC has better fluidity.
[0090] (2) When the mass ratio of the purified water in step S2 to the purified water in step S1 is 1:3.8-7.0, SMCC can have better fluidity (the measured angle of repose is smaller). This is because: under this ratio: the purified water in step S1 can effectively soften the colloidal silicon dioxide and microcrystalline cellulose particles, and the purified water in step S2 can promote the better dispersion of colloidal silicon dioxide on the surface and inside of the microcrystalline cellulose particles.
[0091] Examples 10-11 and Comparative Examples 8-9: Effect of stirring blade and cutter speed on SMCC performance
[0092] In Examples 10-11 and Comparative Examples 8-9, silicified microcrystalline cellulose was prepared according to the steps of Example 1, and the only difference from Example 1 was that the rotation speeds of the stirring paddle and the cutter in step S2 were changed. The specific settings are shown in Table 7.
[0093] According to the methods of Examples 10-11 and Comparative Examples 8-9, three batches of silicified microcrystalline cellulose (300 g for each batch) were prepared. According to the method in Example 1, the three batches of silicified microcrystalline cellulose prepared in Examples 10-11 and Comparative Examples 8-9 were tested for performance, and direct compression tablets were prepared to test the thickness and hardness of the direct compression tablets. The test results are shown in Table 7.
[0094] Table 7 Effect of stirring blade and cutter speed on SMCC performance
[0095]
[0096] Analyzing the data in Table 7, we can see that:
[0097] During the wet granulation process, the speed of the stirring paddle and the cutter will affect the fluidity of SMCC; when the stirring paddle speed is 200~250rpm and the cutter speed is 1400~1600rpm, the fluidity of SMCC obtained by wet granulation can be higher than that of spray drying; and when the stirring paddle speed is too large or too small, even if the cutter speed is slowed down or accelerated accordingly, the SMCC will not be popular. This is because: the appropriate stirring paddle speed and cutter speed can make the combination between microcrystalline cellulose and colloidal silicon dioxide closer, and the water at a certain temperature contained on the surface of SMCC during the wet granulation process can make the surface of the obtained SMCC smoother, thereby improving the fluidity of SMCC.
[0098] Example 12: Preparation of SMCC based on wet granulation
[0099] The silicified microcrystalline cellulose was prepared by the following steps (the amount of each raw material was measured by weight):
[0100] S1: 2 parts of colloidal silica (specific surface area 380m 2 / g) and 100 parts of 90°C purified water were put into a homogenizer and stirred at a speed of 1000 rpm for 5 minutes to obtain a colloidal silica dispersion, which was kept warm for later use.
[0101] S2: 98 parts of microcrystalline cellulose (particle size of 80-100 μm, moisture content of 5%) are put into a wet granulator, the stirring paddle speed is set to 200 rpm, the cutting knife speed is set to 1500 rpm, the stirring paddle and the cutting knife are turned on, and then the colloidal SiO2 dispersion prepared in step S1 under insulation is sprayed into the wet granulator at a speed of 300 mL / min, and 20 parts of 25°C purified water are sprayed at the same time. The time for spraying the colloidal SiO2 dispersion and the 25°C purified water is the same. After 5 minutes of spraying, the stirring paddle and the cutting knife are turned off to obtain wet granules.
[0102] S3: Use a sieve with a pore size of 40 mesh (380 μm) to size the wet granules.
[0103] S4: Dry the wet granules after completing step S3 at a drying temperature of 95° C. for 3 hours to obtain dry granules.
[0104] S5: After the dry particles are crushed, they are sized and sieved to obtain silicified microcrystalline cellulose with a particle size of 100-120 meshes.
[0105] According to the method of this example, three batches of silicified microcrystalline cellulose (300 g for each batch) were prepared. According to the method in Example 1, the three batches of silicified microcrystalline cellulose prepared in this example were tested for performance, and direct compression tablets were made to test the thickness and hardness of the direct compression tablets. The test results are shown in Figure 8.
[0106] Example 13: Preparation of SMCC based on wet granulation
[0107] The silicified microcrystalline cellulose was prepared by the following steps (the amount of each raw material was measured by weight):
[0108] S1: 6 parts of colloidal silica (specific surface area 380m 2 / g) and 100 parts of 90°C purified water were put into a homogenizer and stirred at a speed of 1000 rpm for 5 minutes to obtain a colloidal silica dispersion, which was kept warm for later use.
[0109] S2: 94 parts of microcrystalline cellulose (particle size of 80-100 μm, moisture content of 5%) are put into a wet granulator, the stirring paddle speed is set to 200 rpm, the cutting knife speed is set to 1500 rpm, the stirring paddle and the cutting knife are turned on, and then the colloidal SiO2 dispersion prepared in step S1 under insulation is sprayed into the wet granulator at a speed of 300 mL / min, and 20 parts of 25°C purified water are sprayed at the same time. The time for spraying the colloidal SiO2 dispersion and the 25°C purified water is the same. After 5 minutes of spraying, the stirring paddle and the cutting knife are turned off to obtain wet granules.
[0110] S3: Use a sieve with a pore size of 40 mesh (380 μm) to size the wet granules.
[0111] S4: Dry the wet granules after completing step S3 at a drying temperature of 95° C. for 3 hours to obtain dry granules.
[0112] S5: After the dry particles are crushed, they are sized and sieved to obtain silicified microcrystalline cellulose with a particle size of 100-120 meshes.
[0113] According to the method of this example, three batches of silicified microcrystalline cellulose (300 g for each batch) were prepared. According to the method in Example 1, the three batches of silicified microcrystalline cellulose prepared in this example were tested for performance, and the test results are shown in Figure 8.
[0114] Table 8 SMCC properties of Examples 12 and 13
[0115]
[0116] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0117] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing silicified microcrystalline cellulose based on wet granulation, characterized in that: The following steps are involved: S1: Disperse colloidal SiO2 in water at 70-95°C to obtain colloidal SiO2 dispersion, and keep it warm for later use; S2: adding microcrystalline cellulose to a wet granulator, turning on a stirring blade and a cutting blade, spraying a colloidal SiO2 dispersion and 20-30°C water into the wet granulator for wet granulation, controlling the stirring blade speed to 200-250 rpm, and the cutting blade speed to 1400-1600 rpm, to obtain wet granules; the mass ratio of the 20-30°C water in step S2 to the 70-95°C water in step S1 is 1:3.5-7.0; S3: Drying and pulverizing the wet granules to obtain silicified microcrystalline cellulose.
2. The method for preparing silicified microcrystalline cellulose according to claim 1, characterized in that: In step S1, the temperature of the water is 70-90°C.
3. The method for preparing silicified microcrystalline cellulose according to claim 1, characterized in that: In step S2, the particle size of the microcrystalline cellulose is 80-100 μm; in step S1, the specific surface area of the colloidal SiO2 is 150-380 m 2 / g.
4. The method for preparing silicified microcrystalline cellulose according to claim 1, characterized in that: In step S2, during the wet granulation process, the speed of spraying the colloidal SiO2 dispersion is 250-350 mL / min, and the time of spraying the colloidal SiO2 dispersion and 20-30°C water is the same. The stirring paddle and scraper are turned off 5-10 minutes after spraying the colloidal SiO2 dispersion and 20-30°C water.
5. The method for preparing silicified microcrystalline cellulose according to claim 1, characterized in that: In step S3, before the drying, the wet granules are sized using a 40-60 mesh screen; after the pulverization, the granules are sized again and sieved to obtain silicified microcrystalline cellulose with a particle size of 100-120 mesh.
6. The method for preparing silicified microcrystalline cellulose according to claim 1, characterized in that: In steps S1 and S2, the mass ratio of the colloidal SiO2 to the microcrystalline cellulose is 1:15-49, and the ratio of the total mass of the colloidal SiO2 and the microcrystalline cellulose to the total mass of the water at 70-95°C and the water at 20-30°C is 1:1.0-1.
5.
7. The method for preparing silicified microcrystalline cellulose according to claim 1, characterized in that: The specific process of step S1 includes: stirring colloidal SiO2 and 70-95°C water at a rotation speed of 750-1000 rpm for 5-10 minutes to obtain a colloidal SiO2 dispersion.
8. The method for preparing silicified microcrystalline cellulose according to claim 1 or 3, characterized in that: In step S2, the moisture content of the microcrystalline cellulose is 4-5%.
9. The method for preparing silicified microcrystalline cellulose according to claim 1, characterized in that: In step S3, the drying temperature is 90-95° C. and the drying time is 2.5-3.5 hours.
Citation Information
Patent Citations
Silicified microcrystalline cellulose and preparation method thereof
CN106333928A
Method for preparing pharmaceutic silicified microcrystalline cellulose by silica hydrosol method
CN106377771A